Climate Control Efforts that Impact Flood Disasters in the Lampung - Saputra, Andy Eka; Suprapto, Suprapto; Raharjo, Ismadi (ABEC Indonesia, 2024)
The imbalance between the current availability of water resources and the need for water is an important problem in almost all regions in Indonesia, so that it requires a conception of the engineering and operation of existing facilities. control and utilization of water as well as management carried out efficiently and effectively in order to meet various needs. As an effort to avoid conflicts of interest, an engineering management of dam operations is needed. This raises the idea of ​​the need for water management engineering existing reservoirs. Based on reservoir water inflow and outflow data from 2019 to 2022, optimization was carried out on the Minimum Demand Analysis (Firm Yield Analysis) and Maximum Analysis of Reservoir Water Release using the Non-Linear Generalized Reduced Gradient (GRG) Method. Inflow and outflow data iterations as a function of objectives and constraints Minimize Reservoir Capacity and Amount of water storage in the reservoir = Inflow, and demand at the Way Sekampung Dam = Outflow obtained by Firm Yield Analysis of 335.62 Million M3 or 335 MCM. Thus, it can be concluded that the effective storage volume that can be allocated for irrigation is located between the minimum reservoir elevation at +250 m and the maximum elevation at +255 m. The results of the volume interpolation of the optimization results obtained with an elevation elevation of + 253.74 m, as well as the optimization results for the total release of reservoir water at 281 MCM, so that the management of water resources can then become a benchmark in the distribution of irrigation water, raw water, hydropower and water conservation. continuously